PENGARUH GAYA KEPEMIMPINAN, KECERDASAN EMOSIONAL, DAN KOMUNIKASI PADA KINERJA KARYAWAN CV. BANYU SPA - Tariana, I Wayan Aditya; Loka Natha, I Made Ngurah Erlang; Mandira, I Made Chandra; Linda Kusnita, Kadek; Dewiningrat, Ayu Indira (Universitas Teknokrat Indonesia, 2023)
Cv. Banyu Spa is currently in a state of leadership regeneration. There are differences in leadership styles from new leaders and a generational gap between leaders and employees, it is not uncommon for misunderstandings to occur. This study is intended to investigate the role of leadership style, emotional intelligence, and organizational communication on employee performance through mixed methods approach. The population consists of 32 people using a saturated sample. The research informants were selected using a purposive sampling technique with a total of 5 informants. The research findings have succeeded in proving that a democratic leadership style can improve employee performance. Emotional intelligence through controlling emotions and being sensitive to other feelings is found to be able to motivate employees and produce optimal performance. Organizational communication that runs effectively was found to be able to improve employee performance, but upward communication was identified as not being implemented properly due to gaps in positions that caused employees to be reluctant to communicate directly with leaders. Current study able contribute positively to the human resources literature and practically to Cv. Banyu Spa Bali to improve their emotional intelligence, get closer to employees and adapt their leadership style to the existing circumstances.